Usability measurement of Malaysian online tourism websites - Vatankhah, Najmeh; Koh, Tieng Wei; Letchmunan, Sukumar (Science & Engineering Research Support Society, 2014)
Tourism in Malaysia has huge potential as the country is rich with different kinds of attractions such as historical places, different kinds of festival to enjoy and beautiful scenery to embrace. With the advances of the Internet,many investors have begun to produce different websites to promote their product; however, the quality is still valued expeditiously. The purpose of this paper is to analyze and evaluate the quality of Malaysian tourism websites in terms of usability. With this aim, five different Malaysian tourism websites were selected and evaluated based on their effectiveness, efficiency and user satisfaction. This was done using a questionnaire based evaluation.